(3GdJMaI GddWjaI aj YeGQI GdeSLO GdfHhi hShQ GdeOjfI GdTQjaI (B( (3CjGe GdSdWGf SdjeGf (B)s - (3eMeO Hf NVQ GdQhej GdMfajs
(3ChdgG (B:s
(3CeG HYO agPg fHPI dWjaI hfNHI TQjaI JJVef eG hbY ef GdYeGFQ GdTQjaI dShQ GdeOjfI GdfHhjI hGdeSLO GdTQja hGdefGQI GdSfI , hPdc Cfg deG Cfgi Edi ehdGfG GdSdWGf GdCYXe s
(3BNQgG (B:s
(3Ke eO GdhJQ GdNTj GdPi jhVY YdjgG GdbfGOjd GdUZGQ ai GddjGdi GdTQjaI aRjO ajg ef GdQhVI GdeWgQI Edi MO GdeSLO GdfHhi hcGf ChdkG Edi MO GdQhVI GdeWgQI abW hcGf eJYdbkG Edi LgI GdefHQ GdTQja Je Pdc HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1708/9) s
Keywords: (3GdJGQjNs